Associations between cardiac irradiation and survival in patients with non-small cell lung cancer: Validation and new discoveries in an independent dataset. (December 2021) - Vivekanandan, Sindu; Fenwick, John D.; Counsell, Nicholas; Panakis, Niki; Stuart, Robert; Higgins, Geoff S.; Hawkins, Maria A.
Highlights: Associations between heart doses and survival following RT for LA-NSCLC were analyzed. High left atrial wall volumes receiving 64–73 Gy were associated with poorer survival. This result confirms earlier findings in an independent dataset. Aortic valve volumes receiving 29–38 Gy were also negatively associated with survival. Additionally, mean heart dose was negatively associated with survival. Abstract: Introduction: In ' IDEAL-6′ patients (N = 78) treated for locally-advanced non-small-cell lung cancer using isotoxically dose-escalated radiotherapy, overall survival (OS) was associated more strongly with VLAwall-64-73-EQD2, the left atrial (LA) wall volume receiving 64–73 Gy equivalent dose in 2 Gy fractions (EQD2), than with whole-heart irradiation measures. Here we test this in an independent cohort ' OX-RT' ( N = 64) treated routinely. Methods: Using Cox regression analysis we assessed how strongly OS was associated with VLAwall-64-73-EQD2, with whole-heart volumes receiving 64–73 Gy EQD2 or doses above 10-to-70 Gy thresholds, and with principal components of whole-heart dose-distributions. Additionally, we tested associations between OS and volumes of cardiac substructures receiving dose-ranges described by whole-heart principal components significantly associated with OS. Results: In univariable analyses of OX-RT, OS was associated more strongly with VLAwall-64-73-EQD2 than with whole-heart irradiation measures, but more strongly still with VAortV-29-38-EQD2, the volume of the aortic valve region receiving 29–38 Gy EQD2. The best multivariable OS model included LA wall and aortic valve region mean doses, and the aortic valve volume receiving ≥38 Gy EQD2, VAortV-38-EQD2 . In a subsidiary analysis of IDEAL-6, the best multivariable model included VLAwall-64-73-EQD2, VAortV-29-38-EQD2, VAortV-38-EQD2 and mean aortic valve dose. Conclusion: We propose reducing heart mean doses to the lowest levels possible while meeting protocol dose-limits for lung, oesophagus, proximal bronchial tree, cord and brachial plexus. This in turn achieves large reductions in VAortV-29-38-EQD2 and VLAwall-64-73-EQD2, and we plan to closely monitor patients with values of these measures still >0% (their median value in OX-RT ) following reduction.